(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2018)
This paper has two goals. First, he describes the training that the first generation of educators and teachers went through, who were preparing to start the implementation of bilingual classes in the educational institutions in Vojvodina where they were employed in September 2011. This attempts to highlight examples of good practice and those aspects of training that have not yielded the desired results, with the intention of helping anyone who will organize or conduct similar trainings in the future. Second, the paper presents the first results of measuring the effects of bilingual teaching obtained three years after its introduction. They show that the greatest advantage of students who attend classes in two languages ​​is manifested in the first and second grade of primary school, that the fourth grade is a turning point and that in all other classes students who attend classes only in their mother tongue achieve better results.